Proposal of channel estimation method for bi-directional OFDM based ANC in higher time-varying fading channel - Mata, Tanairat; Naito, Katsuhiro; Mori, Kazuo; Boonsrimuang, Pisit; Kobayashi, Hideo (My University, 2014)
Broadband Analog Network Coding (ANC) based on OFDM has been widely investigated to increase capacity of bi-directional relay communications. The broadband ANC based on OFDM technique is required to estimate channel frequency responses (CFRs) between both user terminals (UTs) and a relay station (RS) precisely so as to remove the self-information data from the received signal and to demodulate the other user's information data with frequency equalization. Many channel estimation methods have been proposed for the OFDM based broadband ANC. However bit error rate (BER) performance of these methods would be degraded relatively in higher time- varying fading channels due to the inaccurate estimation of CFR. To solve this problem, this paper proposes a CFR estimation method which can achieve better BER performance with keeping higher transmission efficiency even in higher time-varying fading channels. The salient features of proposed CFR estimation method are to enable the estimation of combined CFR at the UT for both channels between the UTs and RS by using scattered pilot subcarriers and to enable the demodulation of information data without feedback information of CFR estimated at the RS. This paper presents various simulation results in the higher time-varying fading channels to demonstrate the effectiveness of proposed CFR estimation method for the bi-directional OFDM based ANC.
Keywords: ANC; Bi-directional; CFR; OFDM; Time-varying fading channel